Trophic structure of polychaetes around an offshore gas platform. Issue 1 (15th October 2015) - Punzo, E.; Strafella, P.; Scarcella, G.; Spagnolo, A.; De Biasi, A.M.; Fabi, G.
Highlights: Polychaete trophic groups were studied to detect the effects of a gas platform. The effect of the rig on polychaete assemblage spatial distribution was examined. Polychaete trophic categories can be used as measures of environmental impacts. Abstract: The distribution of polychaetes associated with an offshore gas platform built on a muddy–sandy bottom in the northern Adriatic Sea was investigated with emphasis on their feeding structure. Polychaete species were collected at different distances from the rig using a Van Veen grab. Assessment of the polychaete community and trophic groups for impacts related to the presence of the platform demonstrated significantly different abundances at rising distances from the rig. The present findings highlight an effect of the rig on the spatial distribution of polychaete assemblages. Even though the effects of gas platforms on surrounding benthic communities have been investigated in the Adriatic Sea, no studies have addressed the distribution of polychaete trophic groups along a gradient based on distance from the rig.